Emotion in organizations : a coat of many colors - Troth, Ashlea C.; Humphrey, Ronald H.; Ashkanasy, Neal M., 1945- (Research on emotion in organizations ;, 2024)
Emotions, while extremely varied in their manifestation and effects on organizational settings, nonetheless represent the essence of organizational life. In this 19th volume of Research on Emotion in Organizations, editors Neal M. Ashkanasy, Ronald H. Humphrey and Ashlea C. Troth orchestrate a retrospective view of the field in order to address a wide range of emotion-related topics and point to the future of research in organizational behavior and organization theory. With contributions from Australia, Germany, Finland, Iran, Canada, France, Italy, Poland, the USA and the UK, chapters highlight the diverse nature and effect of emotions in organizational settings. Authors cover topics including physiological needs, strategic investment decisions, workplace supervisory practices, counterproductive behaviors, emotions in teamwork, CEO behavior, emotional intelligence, work-family balance, knowledge sharing and emotional labor. Taking this series' esteemed reputation a step further, Emotion in Organizations: A Coat of Many Colors ushers the field into a new era in the ever-evolving world of work.